The Effect of User Ease and User Security on Purchase Decisions Mediated by Consumer Trust (Study of Tokopedia Users in Sukabumi City) - Maulana, Rizwan; Abdul Aziz, Muh; Antony, Antony (Lafadz Jaya Publisher, 2025)
In the increasingly developing digital era, ease of use and security of use are two important factors that influence consumer trust in the products or services offered. This consumer trust, in turn, can influence the purchasing decisions taken. In this context, understanding the influence of ease of use and security of use on consumer trust, as well as its impact on purchasing decisions, is very important for marketing strategies and product development. This study aims to analyze the influence of ease of use and security of use on consumer trust, as well as its impact on purchasing decisions. The research method uses a quantitative approach with the Structural Equation Modeling (SEM) technique which is analyzed using AMOS software. The sample of this study consisted of 126 respondents who were consumers who used Tokopedia e-commerce. The results of the study indicate that ease of use does not have a significant effect on consumer trust, with a CR value of 1.908 and a p-value of 0.056 which is greater than the significance limit of 0.05, so the first hypothesis is rejected. On the other hand, security of use has a significant and positive effect on consumer trust, with a CR value of 2.428 and a p-value of 0.015 which is smaller than 0.05, so the second hypothesis is accepted. Consumer trust is proven to have a significant effect on purchasing decisions with a CR of 2.415 and a p-value of 0.016, indicating that increasing consumer trust can significantly influence purchasing decisions. Ease of use and security of use were also found to have a significant effect on purchasing decisions, with CR values of 2.346 and 2.303 respectively and a p-value smaller than 0.05, indicating a positive effect of both factors on purchasing decisions. The results of this study provide an important contribution to understanding the factors that influence consumer purchasing decisions, especially in the context of ease of use, security, and consumer trust.